Six metal cations in one double perovskite: exploring complexity of chloride elpasolites by high-throughput experimentation - Stroyuk, Oleksandr; Raievska, Oleksandra; Daum, Manuel; Hauch, Jens; Brabec, Christoph (Journal of Materials Chemistry C, 2024)
A high-throughput screening of lead-free double chloride perovskites Cs2MIMIIICl6 is performed combining combinatorial robot-assisted synthesis with accelerated structural and spectral characterizations. The screening encompasses about 350 elpasolite compounds with broad variations of the MIII site, including combinations of two (Bi + In, Bi + Sb, and In + Sb) and three cations (In + Bi + Sb and Fe + Bi + In). The robot-assisted open-environment synthesis protocol allows the double perovskites with these MIII combinations and Ag+/Na+-occupied MI site to be produced using a general routine in the form of single-phase microcrystalline solid solutions with reliably controlled composition. The high-throughput screening revealed a series of non-additive effects arising from the combination of multiple cations on the MIII site, including a “volcano”-shaped dependence of the photoluminescence quantum yield of Cs2(Ag,Na)(Bi,In)Cl6 elpasolites on Ag/Na and Bi/In ratio and band-bowing effects in the compositional dependences of the bandgaps of perovskites with Bi + Sb, In + Bi + Sb, and Fe + Bi + In combinations. In the latter case, the accelerated screening resulted in the double chloride perovskites with an unusually low indirect bandgap of 1.64 eV.
CRIS-Team Scopus Importer:2024-06-14